FRI0064 Pentoxifylline therapy for remission maintenance in rheumatoid vasculitis. (1st June 2001) - Damian, LO; Rednic, S; Cristea, A; Bolosiu, H
Abstract : Background: Pentoxifylline (PTX), a phosphodiesterase inhibitor, is a vasodilator and antiplatelet drug credited with TNFα transcription inhibition as well. PTX was successfully used in refractory cases of rheumatoid arthritis and in some vasculitides, mainly cutaneous. Objectives: The study aim was to evaluate the efficacy of PTX given as monotherapy after induction of remission in systemic rheumatoid vasculitis (RV). Methods: 12 systemic RV patients (diagnosed according to the Scott&Bacon criteria) were taken into study after the induction of clinical remission (irrespective of the remissive therapy). Each patient received a daily dose of 600 mg PTX. The following were evaluated upon enrollment and after 3 months: clinical signs of vasculitis (on a modified BVAS log), morning stiffness, ESR, CRP and C4 (Mancini), TNFα (ELISA- R&D). The data were compared using the Student?s t test for paired variables. Results: A relapse presenting with constitutional signs appeared only in one of the 12 patients; however, new ocular signs (?red eye?) appeared in 2 patients. Minor cutaneous vasculitis resolved in 1 patient and appeared newly in 3 patients on PTX. Morning stiffness reduced from 107 ± 79 to 75 ± 442 min (p = 0.01). ESR decreased (50.4 ± 21.3 to 42.9 ± 13.8 mm/h, p = 0.02), but CRP and C4 did not vary significantly. TNFα decreased from 4.2 ± 2.5 to 3.8 ± 1.8 ng/ml (p = 0.05). Conclusion: PTX seems to be useful in maintaining the remission of systemic RV and possibly for the prophylaxis of occlusive vasculopathy in these patients. Moreover, PTX is useful also for managing the arthritis of these patients. Its effects in the long-term prevention of relapse of RV have to be evaluated. References: Anaya JM, Espinoza LR. Phosphodiesterase inhibitor pentoxifylline: an antiinflammatory/immunomodulatory drug potentially useful in some rheumatic diseases. J Rheumatol. 1995;22: 595–9 Kitas GD, Bacon PA, Luqmani R. Therapy of other vasculitis syndromes. In: van de Putte LBA, Furst DE, Williams HJ, van Riel PLCM, eds. Therapy of systemic rheumatic disorders . New York: Marcel Dekker, 1998 Maksymowych WP, Avina-Zubieta A, Luong MH, Russel AS. An open study of pentoxifylline in the treatment of severe rheumatoid arthritis. J Rheumatol. 1995;22(4):625–9 Zabel P, Schlaak M, Schade FU. Inhibition of cytokines by pentoxifylline. J Immunobiol. 1993;187:447–63